The Evolution and Performance of Cold-Formed Steel Built-Up Battened Columns - N F Jainudin; Jamaluddin, Norwati; Zainorizuan Mohd Jaini; Hakim S.J.S; Noridah Mohamad (International Journal of Integrated Engineering, 2024)
The cold-formed steel (CFS) built-up battened column represents a transformative and innovative solution in the construction industry due to its versatility, cost-effectiveness, and superior strength-to-weight ratio. In design consideration, chord spacing and batten plates influence the structural performance and stability of the column. The emphasis lies in the design flexibility of built-up battened columns, in which the composite action of several chord members connected by batten plates can enhance axial compressive strength. The batten plate plays a crucial role in preventing buckling and increasing the stability of the column while distributing the load evenly. The batten plates need to be properly designed to ensure stability and reduce buckling failure in the built-up battened column. However, implementing CFS built-up battened columns presents several challenges, including design complexity, connection design, and limited standards and guidelines.